Calidad del servicio y la satisfaccón del cliente en la empresa comercializadora de equipos móviles Claro, Iquitos 2023 - Barabran Palacios, Farah Diva (2025)
In the present study, we sought to find a relationship between service quality and customer satisfaction in the Mobile Equipment Trading Company Claro, Iquitos 2023. A correlational, non-experimental, quantitative design was applied. The sample consisted of 185 subjects. Evaluations were conducted using questionnaires, with a Cronbach's Alpha of 0.892, which validated the use of the questionnaire. Data analysis was performed using SPSS V25, which confirmed that the sample was valid for applying the questionnaire. It was concluded that the variables have a high significant relationship, resulting in a Spearman correlation of 0.509.